The Methodology of Remote Sensing Image Data Scale Space Forming - Wiweka Wiweka; M. Natsir (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2006)
Remote sensing image has information and reality of earth surface content. The principle aim of the producing n-classes object is information extraction. The need of users can be defined correspond to the information scale of object classes, the scale issue is their studying. It will be important as the scaling property has a characteristic hierarchy and link, from the class level of global scale to detail scale. The scaling is performed by using the Gaussian function, the scaling result with factor of more than 100 gives an homogenous image and also object class forms conserving image.Keywords: remote sensing, image, Gaussian, kernel, space, scale.